Stimulating Exchange in International Joint Ventures: An Attachment-based View - Luo, Yadong (Journal of International Business Studies, 2002)
This study distinguishes between personal and structural attachments and examines how these two types of attachments stimulate exchange in IJVs. Analysis of archival and survey data from 255 IJVs in China suggests that both personal and structural attachments contribute to IJV performance, but the rates of contribution of these attachments to IJV profitability diminish as the attachments increase. Moreover, personal and structural attachments strengthen each other in their respective influences on IJV performance.